ChemInform Abstract: The Fifth Element in Drug Design: Boron in Medicinal Chemistry. Issue 52 (24th December 2013) - Kahlert, Jan; Austin, Christopher J. D.; Kassiou, Michael; Rendina, Louis M.
Abstract Review: 59 refs.